THORACIC SURGERY“Open” repair of ruptured thoracoabdominal aortic aneurysm (experience of 51 cases) - Zanetti, Piero Paolo; Krasoń, Marcin; Walas, Ryszard; Cebotaru, Theodor; Popa, Calin; Vintila, Bogdan; Steiu, Flaviu (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Surgical treatment of toracoabdominal aortic aneurysms (TAAA) represents a difficult problem for the vascular surgeon and may become a formidable challenge in an emergency procedure. In patient with hemodynamic instability, protective measures as cerebral spinal fluid drainage and bio-pump against spinal cord, visceral and renal ischemia, may be ineffective or impracticable. Material and methods : We report our experience of 51 emergency-operated patients with TAAA out of 660 treated between 1994 and 2014; 48 patients (94%) were hemodynamically unstable, 3 (6%) were hemodynamically stable. The TAAA patients were evaluated, according to Crawford classification, as: 18 type I, 13 type II, 15 type III, 5 type IV. Results : Overall mortality was 23 cases out of 51 (43.1%); 8 deaths occurred during the surgical procedure and 14 in the postoperative period. Early deaths, subdivided by Crawford TAAA classification, were: type I 9/18 (50%), type II 9/13 (69.2%), type III 7/15 (46.6%), type IV 3/5 (60%). Paraplegia-paraparesis developed in 6 cases out of 43 (16.2%), excluding 8 deaths during the operative procedure. Acute renal failure was observed in 8 out of 43 patients (18.6%). Dialysis was found to be a risk factor for hospital mortality (p = 0.03). Pulmonary insufficiency was diagnosed in 15 patients out of 43 (34.8%), and 5 patients (15.5%) needed tracheostomy, out of whom 3 died (p = 0.04%). Postoperative bleeding was present in 8 cases out of 43 (18.6%). Inferior laryngeal nerve palsy was present in 6 cases out of 43 (13.5%). The follow-up period comprised 1-3-5-10 years postoperative follow-up. The actuarial survival rate of patients discharged from hospital was respectively 75%, 63%, 48%, 35%. Conclusions : In the literature there are very few studies published on emergency treatment for TAAA. Having usually low numbers of patients in the groups wider experiences are still needed to give more light on the pathophysiology and surgical treatment of this type of TAAA, which are still being treated according to the individual surgeon’s experience.